A Letter from the IJNS Issue 7.1 Davis Editorial Fellow - Rachel Brooks (International Journal of Nuclear Security, 2022)
The Davis Editor for Volume 7, Rachel Brooks, reflects on her time as Davis Editor and summarizes the contents of Issue 7.1.